2016
DOI: 10.1016/j.jconrel.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of anti-MDM2 inhibitor SP141-loaded FcRn-targeted nanoparticles to treat breast cancer and metastasis

Abstract: We have recently discovered a specific Murine Double Minute 2 (MDM2) oncogene inhibitor, called SP141, which exerts potent anticancer activity in various breast cancer models. However, its low oral bioavailability is the major hurtle for moving this drug to clinical trial. The present study was designed to discover and validate a novel nano-oral delivery system for this promising anticancer agent. Herein, we report the preparation, characterization, and evaluation of the efficacy and safety of the SP141-loaded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…In the contrast, the antagonists targeting MDM2-p53 binding exert excellent anti-metastasis effects. SP-141, a specific MDM2 inhibitor binding to the hydrophobic pocket occupied by p53, exerts potent therapeutic effects to decrease the tumour growth and inhibit metastasis in breast cancer models ( Wang et al , 2014 ; Qin et al , 2016 ). Furthermore, studies in renal cell carcinoma cells found that MDM2 promotes cell motility and invasiveness through a RING-finger independent mechanism ( Polanski et al , 2010 ), implying that the pro-metastatic functions of MDM2 is not mediated by its E3 ligase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the contrast, the antagonists targeting MDM2-p53 binding exert excellent anti-metastasis effects. SP-141, a specific MDM2 inhibitor binding to the hydrophobic pocket occupied by p53, exerts potent therapeutic effects to decrease the tumour growth and inhibit metastasis in breast cancer models ( Wang et al , 2014 ; Qin et al , 2016 ). Furthermore, studies in renal cell carcinoma cells found that MDM2 promotes cell motility and invasiveness through a RING-finger independent mechanism ( Polanski et al , 2010 ), implying that the pro-metastatic functions of MDM2 is not mediated by its E3 ligase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Other types of MDM2 inhibitors, especially those that directly inhibit MDM2 itself, for example, SP141, JapA, and MA242, should be evaluated for their therapeutic efficacy and safety, as they may provide stronger activity by blocking both the p53‐dependent and p53‐independent functions of MDM2. Further evaluation and development of MDM2 inhibitors for cancer therapy are underway . These studies will provide proof‐of‐principle results to support the therapeutic value of this targeting strategy in drug discovery and may greatly contribute to the development of new therapeutics to treat noncancer diseases.…”
Section: General Discussion and Future Research Directionsmentioning
confidence: 90%
“…Our lab has a long history of developing novel strategies to target MDM2 for cancer therapy and prevention [40][41][42]. In the past, we have identified natural product MDM2 inhibitors such as genistein [43], curcumin [44], and ginsenosides [45][46][47][48][49][50][51][52], and also discovered small-molecule synthetic MDM2 inhibitors such as the SP series [33][34][35][36][53][54][55][56] and synthetic iminoquinones [57][58][59][60][61][62], which have proven effective against several different malignancies. The present study is the first to report the in vitro and in vivo anti-neuroblastoma effects of SP141, a potent and selective MDM2 inhibitor discovered in our lab.…”
Section: Discussionmentioning
confidence: 99%